Impact of Ionospheric Scintillations on GNSS Availability and Precise Positioning - Aguiar, C. R.; Monico, J. F.G. [UNESP]; Moraes, A. O. (American Geophysical Union (AGU), 2025)
For many applications where accuracy, availability, and integrity are essential, such as geodetic positioning and civil aviation, Global Navigation Satellite Systems (GNSS) are indispensable. However, GNSS signal dependability is severely hampered by ionospheric disturbances, especially equatorial plasma bubbles (EPBs), particularly in equatorial latitudes. To better understand how ionospheric irregularities impact GNSS signals across several constellations (GPS, GLONASS, Galileo, BeiDou, and Satellite-Based Augmentation Systems) and frequencies, this study examines ionospheric amplitude scintillation. The objective is to comprehend how these anomalies simultaneously affect GNSS performance in high scintillation activity conditions. The research focuses on the effects of amplitude scintillation during periods of high solar activity by analyzing data from four stations across Brazil. The analysis identified the most critical hours for scintillation events, between 20:00 and 23:59 LST, where up to 13 satellites were simultaneously affected at PRU2, resulting in a notable drop in positioning accuracy. This was further reflected in the degradation of Position Dilution of Precision values, which exceeded 5 in approximately 38% of the cases at Presidente Prudente and São José dos Campos, indicating reduced confidence in positioning accuracy during severe scintillation events. Additionally, the study confirms that lower-frequency signals (L2, G2, B2) are more susceptible to scintillation than higher-frequency signals (L1, G1, E1). Despite multi-constellation capabilities, the simultaneous impact of EPBs on multiple GNSS signals leads to degraded satellite availability and positioning accuracy, especially in regions with high electron density. These findings highlight the need for improved mitigation strategies in multi-constellation systems to enhance GNSS reliability in equatorial regions.
Keywords: amplitude scintillation; EPB; ionospheric irregularities; multi-constellation; multi-frequency; PPP